Optimization of National Downstream Synergy in Realizing Defense Industry Independence to Support the Mission of the Indonesian Air Force - Dedi Dedi; Munawir Sahabuddin; Tri Budianto; Ery Harahap; Asep Kurnia; Yusa Yusa (Jurnal Ar Ro'is Mandalika (Armada), 2026)
This study analyzes the optimization of national downstream synergy as a strategic pathway to achieving defense industry independence in Indonesia, particularly in supporting the operational readiness of the Indonesian Air Force (TNI AU). Using a qualitative descriptive approach, it integrates data from interviews, policy documents, and official reports from the Defense Industry Policy Committee (KKIP), the Ministry of Defense, and PT Dirgantara Indonesia (PTDI). The findings reveal that Indonesia’s defense industry still faces major barriers, including dependence on imported raw materials and technology, low economies of scale, and limited coordination among stakeholders. The study identifies that the success of downstream synergy depends on institutional integration, long-term investment assurance, and technological capability enhancement. Strengthening the roles of KKIP as a policy integrator, the Ministry of Defense as a regulatory and funding enabler, and PTDI as a production executor is essential to align industrial capacity with Air Force requirements. Key strategies include implementing Long-Term Offtake Agreements (LTOA) to stabilize market demand, reforming the Offset and Local Content (IDKLO) mechanism for genuine technology transfer, and integrating upstream industries (PT Inalum, PT Krakatau Steel) to close the material sovereignty gap. The development of MIL-STD-certified testing facilities, local MRO capabilities, and a national defense digital innovation ecosystem will accelerate the transition toward self-reliant production. Ultimately, optimizing national downstream synergy will establish a resilient, competitive, and technologically advanced defense ecosystem capable of independently supporting the Air Force and enhancing Indonesia’s strategic autonomy.